Determinants of the lung microbiome in intubated premature infants at risk for bronchopulmonary dysplasia. (2nd October 2021) - Brewer, Mariana R.; Maffei, Diana; Cerise, Jane; Ahn, Seungjun; DeVoti, James; Codipilly, Champa; Lee, Annette; Weinberger, Barry
Abstract: Background: Airway dysbiosis in premature infants may be associated with bronchopulmonary dysplasia (BPD). Early oropharyngeal colostrum (OPC) administration alters the oral microbiome, which may impact the lung microbiome. We aim to compare the oral and tracheal microbiota during the first week of life, and to determine whether early OPC administration affects microbial diversity or leukocyte inflammatory activity in the lung. Methods: Intubated premature infants ( n = 42) were evaluated. The oral microbiome was characterized on day of life (DOL) 3, and the tracheal microbiome on DOL 3 and DOL 7, using 16S ribosomal DNA sequencing. Gene expression for inflammatory markers was quantified in airway leukocytes by real-time q-PCR. Results: The oral and tracheal microbiota were significantly different on DOL 3, but the tracheal microbiome on DOL 7 was more similar to the oral from DOL 3. Tracheal bacterial diversity decreased from DOL 3 to DOL 7. Longer time to first OPC administration tended to be associated with lower bacterial diversity in the airways. Conclusions: The tracheal microbiome in intubated premature infants in the first week is likely determined, in part, by the composition of the oral microbiome. Bacterial diversity in intubated babies decreases during the first week of life, a pattern that could be consistent with risk for BPD. Decreased bacterial diversity and increased inflammatory activity in the lung may also be associated with delayed administration of OPC.